Enhancement of Flexural Strength in Fiber–Cement Composites through Modification of Sisal Fiber with Natural Rubber Latex and Expanded Perlite - Siriwan Thepruttana; Jira Patthanavarit; Montree Hankoy; Mettaya Kitiwan; Nittaya Keawprak; Phacharaphon Tunthawiroon (Buildings, 2024)
This study presents a novel approach in enhancing the flexural strength of sisal fiber cement composites by employing a dual coating technique with natural rubber latex and expanded perlite to the sisal fibers. The effects of different fiber content (0.25, 0.5, 0.75, 1, 1.25, and 1.5 wt%) and fiber length (1, 2, and 3 cm) on the physical and mechanical properties of sisal fiber cement were also studied. The physical properties, including bulk density and water absorption, were evaluated via the Archimedes method. Flexural strength was measured using the 3-point bending method, and microstructure was observed using a scanning electron microscope (SEM) and an optical microscope (OM). As the fiber content and length increase, the bulk density of the sisal fiber cement decreases. However, composites utilizing coated fibers consistently exhibit a higher bulk density than those utilizing uncoated fibers, attributed to enhanced adhesion and reduced porosity. The water absorption of sisal fiber cement increases with fiber content, but it is mitigated by the natural rubber latex coating, which prevents fiber–water absorption, and by expanded perlite, which reduces voids in the matrix. Composites containing coated fibers consistently exhibit superior flexural strength compared to those with uncoated fibers. The highest flexural strength values of 5.58 MPa were observed in composites utilizing 3 cm of coated fiber with 0.25 wt% fiber content. Microstructure analysis reveals a well-bonded interface in coated fibers, emphasizing the positive impact of coating on mechanical performance. The incorporation of coated sisal fibers effectively improves adhesion, water resistance, and flexural strength, offering sustainable and durable construction materials. The achieved results can serve as the guidelines for the development of a high-performance bio-based construction materials with improved durability and reduced environmental impact.
Keywords: Natural Fiber Reinforced Composites; Innovative concrete reinforcement materials; Innovations in Concrete and Construction Materials